STUDENT ASSESSMENT AND MISCONCEPTIONS OF PHOTOSYNTHESIS: A NOTION OF SHIFTING PERSPECTIVE - Mustafa Kamal Nasution (Jurnal As-Salam, 2018)
Photosynthesis topic is as a compulsory topic ineducation typically in the second year of secondary high school. There is perception of some students that the photosynthesis topic is difficult to learn by student. This paper will clarify questions such as what assessment does mean, what student misconceptions in photosynthesis are, how teachers deal with student misconceptions, and last, why do teachers, school and curriculum need to change perspective in assessment. Based on the discussion, there are some parts that need to be reaffirmed. The teachers should not just recognize assessment as a formal paper, but in term of perspective and classroom instruction. It should be actualized in teaching-learning that there is no judgement of right and wrong for students in leaning. Thus, dealing with student conception could be difficult for the teacher. The principal way is the teacher needs to be clear on the topic’s planning and negotiate the meaning of all representations used in the classroom. Changing the type of assessments does not just simply mean changing teaching strategies or having appropriate types of assessment tool, but it could be a powerful source when it is integrated in the curriculum.